2 - Rethinking Leadership, Management and Career Advancement for 21st Century Deans in the Social Sciences and Humanities at Makerere University - Consolata Kabonesa; Elizabeth Kaase-Bwanga (Journal of Higher Education in Africa, 2014)
The study investigates Leadership, Management and Career Advancement for Female and Male Deans in Social Sciences and Humanities at Make- rere University. The objective is to investigate the gender dynamics of leadership and management in academic careers of deans in Humanities and the Social Sciences and its effect on institutional development. The study is qualitative and quantitative in design, combining both primary and secondary data generated using a questionnaire and face-to-face interviews. The findings indicate that women as well as men face similar challenges in deanship with varying degrees. Factors that motivate male and females into deanship are identified as well as how both male and female deans react to these challenges, and the proposed support for deans’ academic growth. This study provides options for university management on how best university governance and structures should enable the deans to discharge their academic mandates in the most efficient and effective way without compromising the deanship and academic growth of both genders. Overall, the study finds that although there are some significant efforts in place to mainstream gender in leadership and management among others, Make- rere University structures are still in favour of the male gender. There are supportive structures in deanship but no deliberate efforts are in place to encourage women in deanship. The deans know what it takes to advance academically although the environment does not seem to have changed so much to create a level ground for females to compete for leadership posi- tions – something that may negatively impact on institutional development and gender equity in particular. Makerere University needs to rethink its leadership and management strategy to integrate gender fully with a view to becoming more inclusive for institutional development.